2014
DOI: 10.1111/edt.12091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traumatic dental injury on quality of life of Brazilian preschool children and their families

Abstract: The presence of TDI in Brazilian preschool children has no impact on quality of life of the children or their families. However, tooth avulsion is associated with a negative impact on OHRQoL in both groups, and tooth discolouration is associated with a negative impact on family OHRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
142
4
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(181 citation statements)
references
References 31 publications
18
142
4
17
Order By: Relevance
“…A previous study reports that these other variables are predictors of seeking treatment when parents/caregivers are aware of the TDI. 23 Moreover, studies have demonstrated that individuals who live under less privileged conditions, especially those in the age group analyzed herein, visit the dentist less frequently. 12 In the present study, unawareness of the trauma on the part of parents/ caregivers may have exerted an influence on this aspect.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study reports that these other variables are predictors of seeking treatment when parents/caregivers are aware of the TDI. 23 Moreover, studies have demonstrated that individuals who live under less privileged conditions, especially those in the age group analyzed herein, visit the dentist less frequently. 12 In the present study, unawareness of the trauma on the part of parents/ caregivers may have exerted an influence on this aspect.…”
Section: Discussionmentioning
confidence: 82%
“…1 TDI can also have a negative impact on quality of life, 2,3 with physical, esthetic and psychological repercussions that can affect both the child and the parents. 4 The occurrence of TDI in the primary dentition has been associated with accentuated overjet and inadequate lip coverage, 5,6,7,8 as well as behavioral characteristics, such as hyperactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Além do mais, por serem traumas de complexidade menor, a família acaba não dando a atenção necessá-ria, motivo pelo qual o reparo não é imediato 5 . Estudos apontam que traumas leves não impactam negativamente a qualidade de vida de crianças 10,11 , outra razão para a falta de procura por atendimento. Além disso, por se tratar apenas de fratura de esmalte e dentina, sem exposição pulpar, a dor ou a sensibilidade é minimizada, e a busca pelo atendimento, protelada.…”
Section: Discussionunclassified